E-Science and Libraries: Finding the Right Path. - Jennifer Haas; Sharon Murphy (Issues in Science and Technology Librarianship)
The author reflects on issues on electronic science (e-science) and science librarianship discussed at the Re-inventing Science Librarianship forum held in Arlington, Virginia in 2008. One of the topics tackled was the need for science and engineering librarians to include researchers in the existing relationships. Another issue addressed at the forum was the local landscape in the respective universities of librarians. She stresses the role of librarians in light of the emergence of networked, accessible and re-usable data.